Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Penghindaran Pajak dengan Profitabilitas sebagai Variabel Moderasi - Nurifa Laksmitasari Azizah; Imtiyaz Farras Mufidah; Milatina Laksmita Dewi (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study examines food and beverage companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research applies a quantitative approach using secondary data obtained from annual reports and corporate sustainability reports. Purposive sampling was employed to select the research sample, while data analysis was conducted using multiple linear regression and moderated regression analysis. The findings reveal that corporate social responsibility and good corporate governance significantly affect tax evasion practices. In addition, profitability, measured by Return on Assets, is proven to moderate the relationship between corporate social responsibility, good corporate governance, and tax evasion. Firms with higher profitability demonstrate stronger governance and social responsibility effects in reducing tax avoidance behavior. These results indicate that effective governance structures and increased corporate social responsibility can minimize tax evasion, particularly in highly profitable companies. This study contributes to the accounting and taxation literature and provides insights for corporate managers, regulators, and policymakers in formulating strategies to enhance tax compliance and transparency.